Dietary Supplementation with Low-Molecular-Weight Fucoidan Enhances Innate and Adaptive Immune Responses and Protects against Mycoplasma pneumoniae Antigen Stimulation - Hwang, Pai-An; Lin, Hong-Ting Victor; Lin, Hsin-Yuan; Lo, Szu-Kuan (Marine drugs, 2019)
In this study, the low-molecular-weight (LMW) fucoidan, rich in fucose and sulfate, was extracted and purified from the edible brown seaweed, Laminaria japonica. In this study, we orally administered LMW fucoidan to mice for 6 weeks. We then examined fucoidan’s effects on innate immunity, adaptive immunity, and Mycoplasma pneumoniae (MP)-antigen-stimulated immune responses. Our data showed that LMW fucoidan stimulated the innate immune system by increasing splenocyte proliferation, natural killer (NK) cell activity, and phagocytic activity. LMW fucoidan also increased interleukin (IL)-2, IL-4, and interferon (IFN)-γ secretion by splenocytes and immunoglobulin (Ig)-G and IgA content in serum, which help regulate adaptive immune cell functions, and decreased allergen-specific IgE. In MP-antigen-stimulated immune responses, the IgM and IgG content in the serum were significantly higher in the LMW fucoidan group after MP-antigen stimulation. Our study provides further information about the immunomodulatory effects of LMW fucoidan and highlights a potential role in preventing M. pneumoniae infection.